IMPLEMENTASI PENILAIAN RANAH AFEKTIF PADA PEMBELAJARAN BAHASA INDONESIA MI/SD - Sumaryanti, Lilis; Nuraini, Nuraini; Wulansari, Ayu; Abana, Usaid; Utari, Tina (Universitas Muhammadiyah Ponorogo, 2024)
Assessment standards according to Permendikbud No.66/2013 explain that in the 2013 curriculum there are assessment techniques and tools including assessment of attitudes, knowledge and skills aspects. Development of student competence in learning and assessment includes affective, cognitive and psychomotor aspects. In the assessment, the teachers give an attitude value that is appropriate for students to carry out and just to understand students. The results of this study state that aspects of affective assessment in the 2013 curriculum include attitude evaluation consisting of 1) observational assessment by observing students inside and outside the classroom during the Indonesian language learning process; 2) self-assessment is carried out during questions and answers with students; 3) peer-to-peer assessment by conducting positive assessments between students; 4) journal assessment is done by looking at attitudes and student learning outcomes in Indonesian subjects.